Misplaced Pages

Universal generalization

Article snapshot taken from Wikipedia with creative commons attribution-sharealike license. Give it a read and then ask your questions in the chat. We can research this topic together.
(Redirected from Generalization (logic)) Rule of inference in predicate logic
This article includes a list of general references, but it lacks sufficient corresponding inline citations. Please help to improve this article by introducing more precise citations. (March 2023) (Learn how and when to remove this message)
Universal generalization
TypeRule of inference
FieldPredicate logic
StatementSuppose P {\displaystyle P} is true of any arbitrarily selected p {\displaystyle p} , then P {\displaystyle P} is true of everything.
Symbolic statement P ( x ) {\displaystyle \vdash \!P(x)} , x P ( x ) {\displaystyle \vdash \!\forall x\,P(x)}
Transformation rules
Propositional calculus
Rules of inference
Rules of replacement
Predicate logic
Rules of inference

In predicate logic, generalization (also universal generalization, universal introduction, GEN, UG) is a valid inference rule. It states that if P ( x ) {\displaystyle \vdash \!P(x)} has been derived, then x P ( x ) {\displaystyle \vdash \!\forall x\,P(x)} can be derived.

Generalization with hypotheses

The full generalization rule allows for hypotheses to the left of the turnstile, but with restrictions. Assume Γ {\displaystyle \Gamma } is a set of formulas, φ {\displaystyle \varphi } a formula, and Γ φ ( y ) {\displaystyle \Gamma \vdash \varphi (y)} has been derived. The generalization rule states that Γ x φ ( x ) {\displaystyle \Gamma \vdash \forall x\,\varphi (x)} can be derived if y {\displaystyle y} is not mentioned in Γ {\displaystyle \Gamma } and x {\displaystyle x} does not occur in φ {\displaystyle \varphi } .

These restrictions are necessary for soundness. Without the first restriction, one could conclude x P ( x ) {\displaystyle \forall xP(x)} from the hypothesis P ( y ) {\displaystyle P(y)} . Without the second restriction, one could make the following deduction:

  1. z w ( z w ) {\displaystyle \exists z\,\exists w\,(z\not =w)} (Hypothesis)
  2. w ( y w ) {\displaystyle \exists w\,(y\not =w)} (Existential instantiation)
  3. y x {\displaystyle y\not =x} (Existential instantiation)
  4. x ( x x ) {\displaystyle \forall x\,(x\not =x)} (Faulty universal generalization)

This purports to show that z w ( z w ) x ( x x ) , {\displaystyle \exists z\,\exists w\,(z\not =w)\vdash \forall x\,(x\not =x),} which is an unsound deduction. Note that Γ y φ ( y ) {\displaystyle \Gamma \vdash \forall y\,\varphi (y)} is permissible if y {\displaystyle y} is not mentioned in Γ {\displaystyle \Gamma } (the second restriction need not apply, as the semantic structure of φ ( y ) {\displaystyle \varphi (y)} is not being changed by the substitution of any variables).

Example of a proof

Prove: x ( P ( x ) Q ( x ) ) ( x P ( x ) x Q ( x ) ) {\displaystyle \forall x\,(P(x)\rightarrow Q(x))\rightarrow (\forall x\,P(x)\rightarrow \forall x\,Q(x))} is derivable from x ( P ( x ) Q ( x ) ) {\displaystyle \forall x\,(P(x)\rightarrow Q(x))} and x P ( x ) {\displaystyle \forall x\,P(x)} .

Proof:

Step Formula Justification
1 x ( P ( x ) Q ( x ) ) {\displaystyle \forall x\,(P(x)\rightarrow Q(x))} Hypothesis
2 x P ( x ) {\displaystyle \forall x\,P(x)} Hypothesis
3 ( x ( P ( x ) Q ( x ) ) ) ( P ( y ) Q ( y ) ) {\displaystyle (\forall x\,(P(x)\rightarrow Q(x)))\rightarrow (P(y)\rightarrow Q(y))} From (1) by Universal instantiation
4 P ( y ) Q ( y ) {\displaystyle P(y)\rightarrow Q(y)} From (1) and (3) by Modus ponens
5 ( x P ( x ) ) P ( y ) {\displaystyle (\forall x\,P(x))\rightarrow P(y)} From (2) by Universal instantiation
6 P ( y )   {\displaystyle P(y)\ } From (2) and (5) by Modus ponens
7 Q ( y )   {\displaystyle Q(y)\ } From (6) and (4) by Modus ponens
8 x Q ( x ) {\displaystyle \forall x\,Q(x)} From (7) by Generalization
9 x ( P ( x ) Q ( x ) ) , x P ( x ) x Q ( x ) {\displaystyle \forall x\,(P(x)\rightarrow Q(x)),\forall x\,P(x)\vdash \forall x\,Q(x)} Summary of (1) through (8)
10 x ( P ( x ) Q ( x ) ) x P ( x ) x Q ( x ) {\displaystyle \forall x\,(P(x)\rightarrow Q(x))\vdash \forall x\,P(x)\rightarrow \forall x\,Q(x)} From (9) by Deduction theorem
11 x ( P ( x ) Q ( x ) ) ( x P ( x ) x Q ( x ) ) {\displaystyle \vdash \forall x\,(P(x)\rightarrow Q(x))\rightarrow (\forall x\,P(x)\rightarrow \forall x\,Q(x))} From (10) by Deduction theorem

In this proof, universal generalization was used in step 8. The deduction theorem was applicable in steps 10 and 11 because the formulas being moved have no free variables.

See also

References

  1. Copi and Cohen
  2. Hurley
  3. Moore and Parker
Categories: